Microdeformation in poly-L-lactide and poly-L-lactide + hydroxyapatite nanocomposite thin films - Månson, Jan-Anders E. (2013)
In order to gain new insight into failure mechanisms in poly-L-lactide (PLLA) and PLLA + hydroxyapatite nanocomposites, transmission electron microscopy has been used to investigate room temperature microdeformation in electron transparent thin films of these materials subjected to various heat treatments and deformed in tension using the “copper grid” technique. In amorphous PLLA the dominant microdeformation mechanism was crazing. Localized fibrillar deformation zones (DZs) were also observed in semicrystalline films, tending to propagate in regions where the lamellar trajectories were at high angles to the tensile axis. Thus, in spherulitic films, in which the lamellae formed well-defined stacks with approximately straight trajectories at the scale of the spherulite radii, individual DZs were observed to propagate over relatively large distances, as in the amorphous films. On the other hand, films cold crystallized by heating from the glassy state showed more homogeneous lamellar textures. These were associated with a relatively high density of low aspect ratio DZs. Addition of well dispersed nanosized hydroxyapatite (nHA) to the amorphous PLLA films was also found to result in an increase in the craze density, attributed to stress concentrations associated with void formation at the PLLA-particle interfaces during deformation. However, interpretation was less straightforward in cold crystallized PLLA + nHA thin films, owing to a correlation between the lamellar texture and the nHA particles. In this case, both void formation and favorable lamellar orientations may have contributed to initiation of the DZs in the vicinity of the particles. The results are argued to be broadly consistent with previous observations of the behavior of bulk PLLA and PLLA + nHA films with a range of microstructures, in which there was evidence for an improvement in ductility in the presence of the nHA, again attributed to voiding at the PLLA-particle interfaces.